2017
DOI: 10.3389/fmicb.2017.01776
|View full text |Cite
|
Sign up to set email alerts
|

The Oleaginous Yeast Meyerozyma guilliermondii BI281A as a New Potential Biodiesel Feedstock: Selection and Lipid Production Optimization

Abstract: A high throughput screening (HTS) methodology for evaluation of cellular lipid content based on Nile red fluorescence reads using black background 96-wells test plates and a plate reader equipment allowed the rapid intracellular lipid estimation of strains from a Brazilian phylloplane yeast collection. A new oleaginous yeast, Meyerozyma guilliermondii BI281A, was selected, for which the gravimetric determination of total lipids relative to dry weight was 52.38% for glucose or 34.97% for pure glycerol. The lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…Shake flask cultivations were performed using different carbon sources and C/N ratios to test the ability of M. guilliermondii BI281A to convert the substrates into biomass and to produce lipids or other metabolites and to define ideal growth conditions that could be used to run experiments in bioreactors. The ability of M. guilliermondii BI281A cells to produce lipids was first reported using fluorescence intensity using Nile Red dye by high throughput screening (HTS) methodology . The yeast M. guilliermondii BI281A showed higher Relative Fluorescence Units (RFU) than Y. lipolytica , the positive control, proving that this yeast is able to accumulate oil intracellularly .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Shake flask cultivations were performed using different carbon sources and C/N ratios to test the ability of M. guilliermondii BI281A to convert the substrates into biomass and to produce lipids or other metabolites and to define ideal growth conditions that could be used to run experiments in bioreactors. The ability of M. guilliermondii BI281A cells to produce lipids was first reported using fluorescence intensity using Nile Red dye by high throughput screening (HTS) methodology . The yeast M. guilliermondii BI281A showed higher Relative Fluorescence Units (RFU) than Y. lipolytica , the positive control, proving that this yeast is able to accumulate oil intracellularly .…”
Section: Resultsmentioning
confidence: 99%
“…The ability of M. guilliermondii BI281A cells to produce lipids was first reported using fluorescence intensity using Nile Red dye by high throughput screening (HTS) methodology . The yeast M. guilliermondii BI281A showed higher Relative Fluorescence Units (RFU) than Y. lipolytica , the positive control, proving that this yeast is able to accumulate oil intracellularly . Other authors used fluorescence staining and observed lipid particles using Nile Red dye in M. guilliermondii Pcla22 and demonstrated that this yeast can synthetize intracellular lipids .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations